The Non-Uniform Communication Performance of Adaptive Routing for Hierarchical Interconnection Network for 3D VLSI - Miura, Yasuyuki; Watanabe, Shigeyoshi; Rahman, M.M. Hafizur (Discoveries in Agriculture and Food Sciences, 2015)
The Tori-connected mESH (TESH) Network is a k-ary n-cube networks of multiple basic modules, in which the basic modules are 2D-mesh networks that are hierarchically interconnected for higher level k-ary n-cube networks. Many adaptive routing algorithms for k-ary n-cube networks have already been proposed. Thus, those algorithms can also be applied to TESH network. We have proposed three adaptive routing algorithms - channel-selection, link-selection, and dynamic dimension reversal - for the efficient use of network resources of a TESH network to improve dynamic communication performance. In this paper, we have evaluated the dynamic performance of a TESH network using different non uniform traffic patterns. In this paper, we have evaluated by local communication traffic pattern in addition to the hotspot, perfect shuffle, and complement traffic patterns. It was shown that the dynamic communication performance was improved when inter-BM communication appeared frequently such as perfect shuffle and local communication traffic patterns.